2022
DOI: 10.1002/ndr2.12064
|View full text |Cite
|
Sign up to set email alerts
|

First report of Phytophthora pluvialis in Europe causing resinous cankers on western hemlock

Abstract: Severe decline was observed on a mature stand of western hemlock (Tsuga heterophylla) (Fig. 1) in late August 2021 during the Forestry Commission's annual aerial surveillance for Phytophthora ramorum in south-west England. Site visits followed in September to investigate the cause of the decline. Affected trees showed crown dieback, nee-This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Sarg. (western hemlock) in the United Kingdom (Pérez-Sierra et al 2022). In New Zealand, the pathogen was first detected in the eastern North Island in 2008 (Dick et al 2014) and is now found throughout the country (Graham et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Sarg. (western hemlock) in the United Kingdom (Pérez-Sierra et al 2022). In New Zealand, the pathogen was first detected in the eastern North Island in 2008 (Dick et al 2014) and is now found throughout the country (Graham et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Of note is that P. nemorosa has recently been detected once in Belgium (Kurt Heungens, personal communication), as well as in Croatia on nursery stock imported from another EU country (Zeljko Tomić, personal communication). The final species in the clade, P. pluvialis , was first reported from Oregon (Reeser et al., 2013 ), has been introduced to New Zealand (Dick et al., 2014 ; Tabima et al., 2021 ) and has recently been reported from the United Kingdom (Pérez‐Sierra et al., 2022 ) and Belgium (Pirronitto et al., 2024 ). The species was believed to originate from western North America, but it is possible that its origins lie elsewhere, particularly given its destructive behaviour to North American conifer species both in North America and the United Kingdom.…”
Section: Discussionmentioning
confidence: 99%
“…Following a report of Phytophthora pluvialis in the United Kingdom in 2021 (Pérez‐Sierra et al., 2022), surveillance for this forest pathogen started in 2023 in southern Belgium. Douglas fir ( Pseudotsuga menziesii ) was surveyed as it is an economically important conifer species and a major host for P. pluvialis .…”
Section: Figurementioning
confidence: 99%